Study of Atmospheric Composition and Structure: Understanding the Interactions and Impacts of Air Quality on Global and Regional Scales (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Air quality transcends all scales with in the atmosphere from the local to the global with handovers and feedbacks at each scale interaction. Air quality has manifold effects on health, ecosystems heritage and, climate. In this review the state of scientific understanding in relation to global and regional air quality is outlined. The review discusses air quality, in terms of emissions, processing and transport of trace gases and aerosols. New insights into the characterization of both natural and anthropogenic emissions are reviewed looking at both natural (e.g. dust and lightning) as well as plant emissions. Trends in anthropogenic emissions both by region and globally are discussed as well as biomass burning emissions. In terms of chemical processing the major air quality elements of ozone, non-methane hydrocarbons, nitrogen oxides and aerosols are covered. A number of topics are presented as a way of integrating the process view into the atmospheric context these include the atmospheric oxidation efficiency, halogen and HOx chemistry, nighttime chemistry, tropical chemistry, heat waves, megacities, biomass burning and the regional hot spot of the Mediterranean. New findings with respect to the transport of pollutants across the scales are discussed, in particular the move to quantify the impact of long-range transport on regional air quality. Gaps and research questions that remain intractable are identified. The review concludes with a focus of research and policy questions for the coming decade. In particular, the policy challenges for concerted air quality and climate change policy (co-benefit) are discussed. (C) 2009 Elsevier Ltd. All rights reserved.